Laju Penetasan Telur Penyu Dengan Substrat Yang Berbeda Di Kabupaten Gorontalo Utara - Ramin Taib; Sri Yuningsih Noor; Ida Astuti (Universitas Gorontalo, 2019)
The aim of the study was to determine the rate of hatching of turtle eggs with different substrates in North Gorontalo Regency. The research method is an experiment with a Complete Randomized Design (CRD), which is 3 treatments and 3 repetitions obtained from direct observations in the field will be analyzed quantitatively and qualitatively. The treatment consists of Treatment A (Control ie sand from natural nests), Treatment B (coarse sand with a diameter of 0.50-1.00 mm) and Treatment C (fine sand with a diameter of 0.10-0.21 mm. Based on the results of the research on turtle egg hatching with different substrates in the District of Monano, North Gorontalo Regency, it was shown that the average hatching of turtle eggs was the highest at treatment B which was 78%, then treatment A which was 50% and the lowest was in treatment C namely 39%.